Study on adsorptive capability of acid activated charcoal for desulphurization of model and commercial fuel oil samples. Issue 4 (August 2018) - Shah, Syed Sikandar; Ahmad, Imtiaz; Ahmad, Waqas; Ishaq, Muhammad; Gul, Kashif; Khan, Razia; Khan, Hizbullah
Graphical abstract: Highlights: Activated charcoal was chemically modified with hydrochloric acid for the selective liquid-phase desulphurization of the model and real oil samples. DBT adsorption from the model oil follows pseudo-second order kinetics. The experimental data best fitted to both the Langmuir and Freundlich isotherm model. Spent adsorbent was reused and regenerated with toluene washing for multiple consecutive cycles. Abstract: The present study was planned to explore the selective desulphurization efficiency of the acid-modified activated charcoal (AC) as an adsorbent. The oil samples selected were the model oil and the commercial kerosene & diesel. The adsorption capacity of the AC was evaluated for the removal of one of the sulfur analogs i.e. dibenzothiophene (DBT) present in the fuel samples under a set of experimental conditions. The kinetics and thermodynamics of the DBT desulphurization were studied. It was observed that the adsorption firmly followed pseudo-second order kinetic model. Moreover, the experimental value of the amount of DBT adsorbed at equilibrium "qe " was nearly equal to the value calculated from the pseudo-second order kinetic model. Langmuir and Freundlich adsorption isotherm models were applied and the experimental data best fitted with the Langmuir and Freundlich adsorption isotherm models. Compared to other commercially available adsorbents, the acid-modified AC was found to be cost-effective, highly efficient and selective for the DBT removal from the model as well as real petroleum based oils.